2019
DOI: 10.1038/s41416-019-0573-8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanisms to osimertinib in EGFR-mutated non-small cell lung cancer

Abstract: Osimertinib is an irreversible, third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor that is highly selective for EGFR-activating mutations as well as the EGFR T790M mutation in patients with advanced non-small cell lung cancer (NSCLC) with EGFR oncogene addiction. Despite the documented efficacy of osimertinib in first- and second-line settings, patients inevitably develop resistance, with no further clear-cut therapeutic options to date other than chemotherapy and locally ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
854
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 900 publications
(872 citation statements)
references
References 109 publications
(274 reference statements)
16
854
0
2
Order By: Relevance
“…This result was not confirmed by a study from Labbé et al, that found no differences in ORR of patients treated with third generation TKIs, based on TP53 mutation status; this could be for the small size of the analyzed case series [28]. In the light of the paradigm shift brought by FLAURA trial [5], there is a need to identify which biomarkers could predict primary resistance to osimertinib as a first line therapy; if confirmed in a larger case series treated with third generation TKI in the first line, these results could help to better stratify patients, suggesting an EGFR-independent mechanism of resistance, as others have already highlighted [30].…”
Section: Discussionmentioning
confidence: 96%
“…This result was not confirmed by a study from Labbé et al, that found no differences in ORR of patients treated with third generation TKIs, based on TP53 mutation status; this could be for the small size of the analyzed case series [28]. In the light of the paradigm shift brought by FLAURA trial [5], there is a need to identify which biomarkers could predict primary resistance to osimertinib as a first line therapy; if confirmed in a larger case series treated with third generation TKI in the first line, these results could help to better stratify patients, suggesting an EGFR-independent mechanism of resistance, as others have already highlighted [30].…”
Section: Discussionmentioning
confidence: 96%
“…The L747P single mutation appears to be sufficient to confer resistance to erlotinib or gefitinib [98][99][100] if it occurs spontaneously but does not appear to arise in response to gefitinib/erlotinib treatment. Other mechanisms of resistance including mutations or upregulation of other pathways have also been documented [101,102] but we do not discuss them here.…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…3 The systemic therapies of NSCLC have revolutionized over recent years. Recently, the great success of the clinical application of epidermal growth factor receptor (EGFR) 4 and immune checkpoint 5,6 targeted therapies has significantly prolonged the overall survival rate of advanced NSCLC patients. However, owing to the low response rate and the intrinsic and acquired resistance, new treatment strategies are still an urgent demand.…”
Section: Introductionmentioning
confidence: 99%